2003
DOI: 10.1177/0731684403027610
|View full text |Cite
|
Sign up to set email alerts
|

Active Stiffening and Active Damping Effects on Closed Loop Vibration Control of Composite Beams and Plates

Abstract: The influences of active stiffening (displacement control) and active damping (velocity control) effects introduced by collocated piezoelectric actuators and sensors on vibration control of composite structures are studied in this paper. A nine-node piezoelectric plate finite element is derived using the first order shear deformation theory to model the distributed actuation and sensing numerically. An output feedback control strategy is developed with the linear quadratic regulator theory in modal domain to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The numerical analyses indicate that the natural frequencies and the corresponding modes of the laminated structures with two sets of PZT elements can be significantly altered by induced in-plane stresses. The impact of the stiffening and damping effects due to piezoelectric actuators and sensors on the composite structures vibrations control has been studied by Raja et al [15]. Authors observe that the stiffening effect caused by the active element is more pronounced for the vibrations of relatively high amplitudes.…”
Section: Introductionmentioning
confidence: 95%
“…The numerical analyses indicate that the natural frequencies and the corresponding modes of the laminated structures with two sets of PZT elements can be significantly altered by induced in-plane stresses. The impact of the stiffening and damping effects due to piezoelectric actuators and sensors on the composite structures vibrations control has been studied by Raja et al [15]. Authors observe that the stiffening effect caused by the active element is more pronounced for the vibrations of relatively high amplitudes.…”
Section: Introductionmentioning
confidence: 95%
“…The feedback voltage is obtained by amplifying the sensor signal with a suitable gain. The experimental implementation of displacement and velocity feedback using PZT sensors has been broadly discussed [23].…”
Section: Active Vibration Control Studies On the Active Aeroelastimentioning
confidence: 99%
“…Rao and Ganesan presented the harmonic response of tapered composite beams by using the finite element method [3]. Raja et al [4] presented the free and forced harmonic vibration control of composite beams by active stiffening method using piezo patches. They reported that the active stiffening effect through displacement control is more effective for smaller modes.…”
Section: Introductionmentioning
confidence: 99%